ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN (Pengguna Apple iPhone di Jurusan Manajemen Universitas Diponegoro Semarang) - Utami, Ayu Arunika; Khasanah, Imroatul (Diponegoro Journal of Management, 2016)
This study aims to analyze the influences of product quality, service quality and brand image to customer loyality of Apple Iphone products through customer satisfactions as intervening variable on apple Iphone users in Management Program, Diponegoro University Semarang. Product quality, service quality and brand image are the reasons of consumer when selecting and also repurchasing smartphone products which is one of important needs in this digital era.Non probability samping was used for sampling. Data were collected from 100 respondents which were selected using criteria of judgement that should using Apple Iphone as their phone. Questions were given with using questionnaire which consists of open and closed questions. Respondent responses were analyzedÂ  with multiple linear regression using SPSS v.21.0. Can be concluded that product quality, service quality, and brand image giving positive and significant influences to customer satisfaction. After that, customer satisfaction has positive and significant influence to customer loyality of Apple Iphone Users in Management Program, Diponegoro University Semarang.